Strategi Kodam III/Siliwangi dalam Pemberdayaan Wilayah Pertahanan untuk Ketahanan Nasional - Hipni Maulana Farhan; Hariyono Hariyono; Sri Rusyono S (Mahesa Research Center, 2024)
Strengthening Indonesia's national defense in facing various threats, both physical and non-physical. This strengthening includes the modernization of military equipment, community empowerment through territorial development programs, and increased coordination between regions. Kodam III/Siliwangi plays an important role in maintaining the stability of the West Java and Banten regions, especially in the face of the threat of terrorism, natural disasters, and cyber attacks. This study aims to analyze the strategy of Kodam III/Siliwangi in empowering land defense areas to realize national resilience. The focus of the research includes the modernization of military equipment, community empowerment through territorial development programs, and improved coordination between regions to deal with various threats, both physical and non-physical. Kodam III/Siliwangi, as the subject of the research, plays a strategic role in maintaining the stability of the West Java and Banten regions, especially in dealing with the threat of terrorism, natural disasters, and cyber attacks. The research method used is qualitative descriptive with SWOT analysis. The results of the study show that Kodam III/Siliwangi implements an aggressive strategy through optimizing disaster-resilient infrastructure, strengthening cyber capacity, and continuous human resource training, thereby increasing operational readiness in facing physical and digital threats. Collaboration with local governments, educational institutions, and research strengthens integrated defense planning. In addition, local economic development through partnerships with the private sector and community empowerment supports social and economic stability, making the region more adaptive to various conventional and non-conventional challenges.